Management by projects achieving success in a changing world - Hamilton, Albert (Thomas Telford, 1997)
Provides a comprehensive description and analysis of the skills involved in project management, beginning with a look at the importance of change in organisations. This book emphasises the benefits of taking a 'systems' approach to management, and illustrates how 'projects' form a major part of the day-to-day running of any business.